Hermeneutyka pojęcia evangelical w Evangelical Catholicism George'a Weigla - Wielgosz, Karol (Poznańskie Studia Teologiczne, 2015)
George Weigel, in his recent book Evangelical Catholicism, proposed a vision of the reform of the life of the Church. Because this Catholic theologian is widely known and respected, his book was translated into many languages and influenced the discussion about the shape of Catholicism in the 21st century. It seems desirable to learn more about Weigel’s proposal. The article is an attempt to analyze Weigel’s idea. In order to do so, we will try to scrutinize the full notion of the term evangelical, which describes the vision of Catholicism according to Weigel. For this reason the first section of the article contains a linguistic analysis of the different Polish equivalents of the English word: evangelical. The second section is a description of the vision of George Weigel. The third section answers the question if one can say that the vision of Catholicism by George Weigel has certain evangelical (that means: according to the basics of the Evangelical Movement) characteristics. The conclusion of the analysis undertaken in the article is that the vision of Catholicism presented by George Weigel is not only compatible with the Gospel but resembles in certain aspects the ideas of Evangelicalism. As such it can be helpful in the fostering of ecumenical dialog.